Exploring visual embodiment effect in dark tourism: The influence of visual darkness on dark experience. (April 2022) - Lv, Xingyang; Lu, Ruihua; Xu, Shuangyu; Sun, Jiaojiao; Yang, Yang
Abstract: Research in dark tourism has been ongoing for over two decades. Although in practice, many dark tourism destinations adjusted the lighting of the display environment to influence tourist experience, little is known about the sensory stimulation of non-text related content (e.g., lighting of the environment or darkness of visual materials) on dark tourists' psychological experience. This study examined the influence of visual darkness on tourists' dark experience and explored the relationship between visual darkness and psychological darkness through a content analysis of online comments and photos for 30 dark tourism destinations worldwide, followed by four experiments. Results showed that the stimulation of visual darkness affected dark tourists' psychological experience and behavioral intentions (including recommendation intention and touch preference), and such embodied effect existed in both two-dimensional plane and three-dimensional space. The study provides many practical implications for experience creation of dark tourism destinations. Highlights: Visual embodiment effect was explored and identified in dark tourism. Situational and field experiments were conducted to examine such effect. Both two and three dimensional visual darkness affect tourists' dark experience. Visual sensory stimulation affects both tourists' psychological state and behaviors. A non-mental relationship between visual and psychological experience was established.